Etika dan Budaya Perusahaan Syariah di KSU BMT Mujahidin Pontianak - Armia Hidayati; Vifi Alaeda (Jurnal Pelita Nusantara, 2026)
This study examines the implementation of ethical and corporate culture based on Sharia principles at KSU BMT Mujahidin, an Islamic financial institution. The organization not only focuses on professional achievements and work targets but also integrates Islamic values into all aspects of its operations. The ethical framework emphasizes honesty, responsibility, discipline, and commitment to worship and moral values. Employee evaluations are conducted holistically, considering moral and spiritual aspects while involving both supervisors and colleagues in the assessment process. Additionally, the institution regularly holds training sessions and religious studies to enhance employees' understanding of Sharia principles. In addressing ethical violations, the approach prioritizes guidance and discussion over punitive measures. KSU BMT Mujahidin is also actively engaged in religious-based social programs, which strengthen solidarity among employees and foster social awareness. By implementing a Sharia-compliant management system, the institution strives to create a conducive, productive, and value-oriented work environment in accordance with Islamic principles.